Eriophyoid mite fauna of Shaanxi Province, China, with descriptions of five new species (Acari: Eriophyoidea) - Xue, Xiao-Feng; Han, Xiao; Song, Zi-Wei; Hong, Xiao-Yue (Zootaxa, 2012)
Prior to this research, 47 genera and 124 eriophyoid mite species have been known to occur in Shaanxi Province, north-western China. We described and illustrated herein five new species collected in Shaanxi Province. They are Proartacriscathayensis sp. nov. on Carya cathayensis Sarg. (Juglandaceae), Acaphyllisa changqingiensa sp. nov. on Salix sp. L. (Sal-icaceae), Tegonotus albus sp. nov. on Cornus alba L. (Cornaceae), Phyllocoptruta japonica sp. nov. on Lonicera japonicaThunb. (Caprifoliaceae), Anthocoptes albosinensis sp. nov. on Betula albosinensis Burkill (Betulaceae). At the same time,one new eriophyoid mite record from China is provided, Rhinotergum schestovici Petanovic, 1988, rec. nov. on Betulaalbosinensis Burkill (Betulaceae). A list of eriophyoid mites from Shaanxi Province is provided. All the new species and new record described herein are vagrants on respective host plants.